Accelerometer-Measured Daily Steps, Physical Function, and Subsequent Fall Risk in Older Women: The OPACH Study. (17th December 2021) - Schumacher, Benjamin; Bellettiere, John; LaMonte, Michael; LaCroix, Andrea
Abstract: We sought to investigate the association between steps per day (steps/d) and incident fall risk while also assessing the role of physical functioning on this association. Steps/d were measured by accelerometer for 7 days in 5, 545 women aged 63 to 97 years between 2012 - 2014. Falls were ascertained from daily fall calendars for 13 months. Median steps/d were 3, 216. There were 5, 473 falls recorded over 61, 564 fall calendar months. The adjusted incidence rate ratio comparing women in the highest vs. lowest step quartiles was 0.71 (95% confidence interval, 0.54 - 0.95; P-trend across quartiles of steps/d = 0.01). After further adjustment for physical function using the Short Physical Performance Battery, the rate ratio was 0.86 (0.64-1.16; P-trend = 0.27). Mediation analysis estimated that 66.7% to 70.2% of the association of steps/d and fall risk may be mediated by physical function. In conclusion, higher steps/d were related to lower incident falls primarily through their beneficial association with physical functioning. Interventions that improve physical function, including those that involve stepping, could reduce falls in older adults.